Aider les enseignants débutants à problématiser la conception de situations d’enseignement-apprentissage - Bruno Lebouvier; Florian Ouitre; Philippe Briaud (Recherches en Éducation)
Using problematisation as a theoretical framework, this paper explores different means to help new teachers design their lessons. Lesson design needs to factor in various learning parameters, including pupils backgrounds as well as their empirical constraints. The paper analyses three distinct teaching environments from the point of view of the problematisations generated. The results of the study offer an opportunity to compare the dynamics of these problematisations and to consider specific and complementary ways of working.